THE MEANING OF RELIGIOUS MODERATION ON THE RESILIENCE OF MUSLIM MINORITY IN BALINESE HINDUS - Amin Tohari; Moch. Khafidz Fuad Raya (UIN Sumatera Utara, 2021)
Abstract: The Bali bombing around two decades ago has caused deep traumatic events in the world, not only psychological, socioeconomic, and multinational effects, but also serious impacts on the relationship between the two religions: Islam and Hindusm. This study documents how Muslims as a minority group in Bali attempted to survive amidst the Hindu majority and how these two ethnic-religious groups maintain harmonious relationship after the Bali Bombing incident. This study uses a case study methods with an interpretive paradigm and qualitative approach, the aim is to shows that social pressure and discrimination has not harm the relationship between the two in that the Muslim and Hindus cooperate in the economic sector and strengthen the relationship with kinship and marriage. This effort is a way for the Muslim-Hindus to rebuild the moderation of unity which was collapsed in Bali.Keywords: Muslim-Hindus, Bali, majority-minority, relations